pH-responsive nanozymes: multifunctional platforms for biomedical catalysis toward clinical translation - Zhuang, Xiaofei; Gao, Shanshan; Tao, Yueqin; Yuan, Mujie; Han, Zhiwu; Wang, Ying (Frontiers in Bioengineering and Biotechnology, 2026)
As an emerging class of smart nanomaterials, pH-responsive nanozymes are capable of realizing dynamic regulation of catalytic activity according to microenvironmental acidity and alkalinity. The material system encompasses noble metals, metal oxides, metal sulfides, carbon-based nanozymes, and metal-organic frameworks. Through engineering strategies such as surface ligand modification, heterogeneous atom doping and core-shell structure design, these nanozymes can achieve precise response to complex biological microenvironments, and show unique catalytic properties in the lesion site with specific pH. In recent years, pH-responsive nanozymes have been applied in various biomedical fields, such as tumor therapy, antimicrobial, wound healing, and anti-inflammation, to enhance therapeutic efficacy through controlled activation and targeted drug delivery. However, they still face many challenges in clinical translation, such as in vivo stability, toxicity assessment and precise regulation of activity. This paper reviews the research progress of pH-responsive nanozyme therapeutic systems and discusses the potential and challenges of integrating them with other nanotechnologies and therapeutic modalities, aiming to provide a reference and outlook for promoting their wider application in clinical diseases.